Sustainable Tourism Competitiveness Enhancement Model in North Buton Regency (Architecture Image Studies, 2025)
This study aims to formulate a model for developing sustainable tourism competitiveness in North Buton Regency, which has a wealth of natural and cultural tourism resources but has not been optimally managed. The study used a qualitative approach with an exploratory design, making North Buton Regency tourism the unit of analysis. Data were collected through field observations, in-depth interviews, and expert judgment with 20 experts from local government elements, tourism actors, academics, community leaders, and tourists, and supported by analysis of regional planning and policy documents. Data were analyzed using the Analytical Hierarchy Process (AHP) method to determine the priority scale of variables and indicators for developing sustainable tourism competitiveness. The results showed that the model for developing sustainable tourism competitiveness in North Buton Regency was influenced by six main variables, namely tourism planning and development policies, core resources and tourist attractions, tourism management, supporting factors of resources, tourism services, and evaluation of destination resilience. In terms of priority, tourism planning and development policies ranked highest, followed by core resources and tourist attractions and tourism management, while supporting factors of resources, tourism services, and evaluation of destination resilience played a role as strengthening factors for sustainability. These findings confirm that developing competitive and sustainable tourism in North Buton Regency must begin with strong political and policy commitment, accompanied by the preservation of natural and cultural resources, effective destination governance, and ongoing evaluation of social, economic, and environmental impacts.